Reconstructing Memory and Decolonizing History: A Critical Study of Andalusian Legacy - LABKADRI, ABDELLATIF (International Journal of Language and Literary Studies, 2025)
This paper investigates the intricate interplay between literary analysis and historical context through the lens of Moroccan historical novels, focusing on Hassan Aourid’s The Morisco. This study highlights the prominence of integrating historical context into literary critique by decolonizing and reimagining the past. The analysis of The Morisco serves as a case study to demonstrate how historical narratives are recontextualized and reinterpreted within the framework of postcolonial discourse. This approach facilitates the text’s understanding by employing an eclectic theoretical framework drawing from, but not limited to, Said, White, and Lukács. It underscores the broader socio-political implications of historical representation in literature. This essay argues that The Morisco deploys historical fiction to decolonize the past by providing a voice for unrepresented subalterns, to use Spivak’s term, the expelled Muslims and Jews from their homeland, Andalucia. It is also argued that Aourid’s historical narrative exemplifies a distinct approach within Moroccan literature, where fictional techniques are intertwined with historiographical ones to decolonize the official history, calling upon the urgent need to reread the past, one that has influenced our contemporary history and to rectify the misrepresentation in historical narratives.